The Relationships between Relatively Cancellation Modules and Certain Types of Modules (Baghdad Science Journal, 2025)
Let R be a commutative ring with identity and M be unitary (left) R-module. The principal aim of this paper is to study the relationships between relatively cancellation module and multiplication modules, pure submodules and Noetherian (Artinian) modules.